1984
DOI: 10.1007/bf00495407
|View full text |Cite
|
Sign up to set email alerts
|

Novel application of aniline blue

Abstract: The present study shows that aniline blue can be used as a fluorescent stain for glycogen. The dye is also helpful in tracing pathological and autolytic changes in lysosomes, mitochondria, erythrocytes and nuclei, and it can also be used for demonstrating bacteria in tissue sections and smears. The techniques used are simple, rapid and inexpensive. Spectrophotometric studies on aniline blue solutions have shown that aniline blue fluorescence was enhanced by the addition of certain proteins, or of glycogen to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

1985
1985
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…Upon comparison between the quantitative image analysis results, for the acquired fluorescent images of the two studies, and the sample glycogen analytical concentration obtained via HPLC, better results were obtained using the 2% alkaline solution [31]. This agreed with the findings of Shennawy et al [31]. Thus, the methodology used for biomass suspension was as follows.…”
Section: Staining Proceduressupporting
confidence: 83%
See 3 more Smart Citations
“…Upon comparison between the quantitative image analysis results, for the acquired fluorescent images of the two studies, and the sample glycogen analytical concentration obtained via HPLC, better results were obtained using the 2% alkaline solution [31]. This agreed with the findings of Shennawy et al [31]. Thus, the methodology used for biomass suspension was as follows.…”
Section: Staining Proceduressupporting
confidence: 83%
“…Intracellular glycogen storage was observed using Aniline blue staining. Although aniline blue is generally used to detect glycogen in tissue sections [31], in activated sludge the application of aniline blue staining procedures for glycogen detection has been questioned and not frequently used due to inconsistent results [32]. In order to try to overcome the limitations of the existing methodologies, two comparative studies (data not shown) were performed using 2% acid solution (acetic acid with pH at 3.5) and alternatively 2% alkaline solution (phosphate buffer with pH at 7.2) during 20 min reaction [31] with biomass suspension.…”
Section: Staining Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…Combined with FISH or otherwise, fluorescent staining samples with DAPI [95], at high concentrations, and Nile blue [96] dyes, can be applied to visualize polyphosphate granules and PHA inclusions, respectively. Furthermore, Shennawy et al [97] reported the use of Aniline blue to stain glycogen inside cells. A more detailed description about the different staining techniques can be found in Serafim et al [75].…”
Section: Fluorescent Stainingmentioning
confidence: 99%